2015
DOI: 10.1152/ajplung.00042.2015
|View full text |Cite
|
Sign up to set email alerts
|

Remodeling of alveolar septa after murine pneumonectomy

Abstract: In most mammals, removing one lung (pneumonectomy) results in the compensatory growth of the remaining lung. In mice, stereological observations have demonstrated an increase in the number of mature alveoli; however, anatomic evidence of the early phases of alveolar growth has remained elusive. To identify changes in the lung microstructure associated with neoalveolarization, we used tissue histology, electron microscopy, and synchrotron imaging to examine the configuration of the alveolar duct after murine pn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 36 publications
1
19
0
Order By: Relevance
“…The lower panels show their counterparts in the case of detergent-rinsed rabbit alveolar ducts. Note that while the secondary septa appear normal in the upper panel, they collapse onto the primary septa in the case of detergent-rinsed lungs, which is very similar to the pneumonectomized case (Ysasi etal., 2015), Left and Middle panels are adapted from Bachofen etal.(1979). D out and D in denote the outer and inner diameter of alveolar duct, respectively; 2H indicates the thickness of interstitial space.…”
Section: Figuresupporting
confidence: 64%
“…The lower panels show their counterparts in the case of detergent-rinsed rabbit alveolar ducts. Note that while the secondary septa appear normal in the upper panel, they collapse onto the primary septa in the case of detergent-rinsed lungs, which is very similar to the pneumonectomized case (Ysasi etal., 2015), Left and Middle panels are adapted from Bachofen etal.(1979). D out and D in denote the outer and inner diameter of alveolar duct, respectively; 2H indicates the thickness of interstitial space.…”
Section: Figuresupporting
confidence: 64%
“…The expansion of the remaining lung is not simple isotropic expansion as there is a commensurate increase in lung weight (3), cell number (4), and alveolar number (5). These observations indicate that post-pneumonectomy lung growth involves fundamental remodeling of the lung microarchitecture (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…Finite element modeling has shown that mechanical stretch-the signal most commonly implicated as a trigger in compensatory growth (1,8)-is maximal in the subpleural alveolar ducts (9,10). In many subpleural alveolar ducts, postpneumonectomy morphometry has demonstrated a retraction of alveolar septa and an increase in alveolar duct diameter (7). The time course of septal retraction suggests that ductal dilatation is followed by scattered cellular proliferation (11), the septal migration of myofibroblasts (12), and subsequent septal thickening (7).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations